PENGARUH ANALISIS PROFITABILITAS & LIKUIDITAS TERHADAP HARGA SAHAM SEKTOR ENERGI 2017-2022 - Taufiqurrahman, Mohammad Aviciena; Sudaryati, Erina (Owner : Riset dan Jurnal Akuntansi, 2024)
The movement of shares can provide advantages and disadvantages to investors. This can be influenced by several things, both internal and external to the company. Fundamental analysis has become highly crucial for both individual and organizational investors. This study examines the effect, whether the variables Return On Equity, Return On Assets, Net Profit Margin, Earning Per Share, and Current Ratio are able to affect stock prices. After obtaining data on the Osiris database and testing with the latest version of Smart Partial Least Square 4.0, it was found that the variables Return On Assets, Return On Equity, Net Profit Margin and Current Ratio do not impact stock prices, while the Earning Per Share variable has an influence on stock prices. stock price.